The improvements of accounting proficiency among female farmers in Wironanggan Village, Gatak District, Sukoharjo Region. - Rochmatullah, Mahameru Rosy; Rafli Rahmad Rifani; Kurnia Riyadi (LPPM ITB AAS Indonesia Surakarta, 2025)
The objective of this Community Empowerment Program is to improve the human capital within the Women Farmers Group (KWT) of Wironanggan Village, Gatak District, Sukoharjo Region. Due to limitations in financial management and human resources, the KWT management is facing difficulties. Therefore, this activity aims to provide training and mentorship specifically in the areas of creating financial reports and monitoring financial performance for KWT. This activity is anticipated to stimulate a growth in the human resource capability to handle financial matters within the company. This activity utilizes an approach that involves training individuals in the preparation of financial reports and the identification of the complete KWT organizational process in order to determine key performance measurement indicators.